Vpliv inercijske vadbe moči na gibalno učinkovitost starostnic - Spudić, Darjan (Šport (Ljubljana), 2017)
Recent studies show that sarcopenia and muscle strength loss can not only be prevented, but the elderly are also able to successfully gain muscle mass, maximum strength and power. Resistance exercise also positively influences functional abilities, independence and active aging. Inertional contraptions are an effective way of resistance exercise among elderly. The contraction of the eccentric part of the muscles generates stronger forces than the concentric part, which is a vital concept of the inertion exercise, also known as eccentric overload. The purpose of the study was to examine practical implication and actual effects of the inertial contraption on functional abilities among elderly women. We compared the effects of traditional resistance exercise in the form of performing squats using the kettlebell and inertional resistance exercise with the constructed inertion contraption for performing squats. We discovered a similar effect of both of the exercise types on the power of the leg extensor muscles tested by the Sit to Stand test. The exercise group using the inertion contraption has provided us with slightly better results. Both of the exercises have not majorly influenced the results of the Functional Reach Test, the Timed Up and Go Test and the 6-minute Walk Test.
Keywords: elderly; inercija; inertia; jo-jo; moč; resistance; sarcopenia; sarkopenija; Sit to Stand; sport; starostnik; šport; vstajanje s stola; Yo-Yo